2005
DOI: 10.1007/s00299-004-0909-5
|View full text |Cite
|
Sign up to set email alerts
|

Excision of a selectable marker in transgenic rice (Oryza sativa L.) using a chemically regulated Cre/loxP system

Abstract: Removal of a selectable marker gene from genetically modified (GM) crops alleviates the risk of its release into the environment and hastens the public acceptance of GM crops. Here we report the production of marker-free transgenic rice by using a chemically regulated, Cre/loxP-mediated site-specific DNA recombination in a single transformation. Among 86 independent transgenic lines, ten were found to be marker-free in the T0 generation and an additional 17 lines segregated marker-free transgenic plants in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
109
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(112 citation statements)
references
References 26 publications
1
109
1
1
Order By: Relevance
“…Similar wide range of excision efficiency was reported in the literature using chemically, or heat shock induced or embryo specific Cre/lox systems (Chong-Perez et al 2012;Liu et al 2007;Zuo et al 2001). Wang et al (2005), however, reported lower variation in heat shock promoter activity. The efficiency of cre transgene activation may depend on the transgene 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 incorporation site or on the developmental stage of the transgenic plants when cre gene activity is induced (Russell et al 1992).…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Similar wide range of excision efficiency was reported in the literature using chemically, or heat shock induced or embryo specific Cre/lox systems (Chong-Perez et al 2012;Liu et al 2007;Zuo et al 2001). Wang et al (2005), however, reported lower variation in heat shock promoter activity. The efficiency of cre transgene activation may depend on the transgene 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 incorporation site or on the developmental stage of the transgenic plants when cre gene activity is induced (Russell et al 1992).…”
Section: Discussionsupporting
confidence: 51%
“…The efficiency of this system differed from our results. The lowest level has been detected in potato shoot internodes (5-14%) (Cuellar et al 2006), Wang et al (2005) have reached 70-80% Cre/lox activity in tobacco seed and leaf, while the excision rate has even reached 100% in tobacco seedlings (Liu et al 2005). Heat shock can cause damage in wheat tissues therefore it is not the most proper way of inducing gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previously developed Cre/loxP-based strategies, transient and stable expression of the Cre recombinase gene has been accomplished using chemical or heat inducible promoters (Hoff et al, 2001;Sreekala et al, 2005;Zhang et al, 2003;Zuo et al, 2001) or tissue-specific promoters (Bai et al, 2008;Luo et al, 2007). It is known that the -46 minimal promoter alone containing a TATA box and transcription start site is unable to drive gene expression in plants (Lim et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…To overcome these shortcomings, an alternative technique was developed in which Cre was included on the same DNA segment as the marker gene flanked by loxP sites (Hoff et al, 2001;Zuo et al, 2001). In this way, an auto-excision system of marker genes was developed under the control of chemical or heat inducible promoters (Hoff et al, 2001;Sreekala et al, 2005;Wang et al, 2005;Zhang et al, 2003;Zuo et al, 2001). Similar auto-excision systems for marker genes have also been developed using pollen-, seed-, or floral-specific promoters (Bai et al, 2008;Luo et al, 2007).…”
Section: Introductionmentioning
confidence: 99%